On site DNA barcoding by nanopore sequencing - Menegon, Michele; Cantaloni, Chiara; Rodriguez-Prieto, Ana; Centomo, Cesare; Abdelfattah, Ahmed; Rossato, Marzia; Bernardi, Massimo; Xumerle, Luciano; Loader, Simon; Delledonne, Massimo (PLOS ONE, 2017)
Biodiversity research is becoming increasingly dependent on genomics, which allows the unprecedented digitization and understanding of the planet’s biological heritage. The use of genetic markers i.e. DNA barcoding, has proved to be a powerful tool in species identification. However, full exploitation of this approach is hampered by the high sequencing costs and the absence of equipped facilities in biodiversity-rich countries. In the present work, we developed a portable sequencing laboratory based on the portable DNA sequencer from Oxford Nanopore Technologies, the MinION. Complementary laboratory equipment and reagents were selected to be used in remote and tough environmental conditions. The performance of the MinION sequencer and the portable laboratory was tested for DNA barcoding in a mimicking tropical environment, as well as in a remote rainforest of Tanzania lacking electricity. Despite the relatively high sequencing error-rate of the MinION, the development of a suitable pipeline for data analysis allowed the accurate identification of different species of vertebrates including amphibians, reptiles and mammals. In situ sequencing of a wild frog allowed us to rapidly identify the species captured, thus confirming that effective DNA barcoding in the field is possible. These results open new perspectives for real-time-on-site DNA sequencing thus potentially increasing opportunities for the understanding of biodiversity in areas lacking conventional laboratory facilities.